Extreme Values of Hemoglobin A1c Are Associated With Increased Risks of Chronic Obstructive Pulmonary Disease in Patients With Type 2 Diabetes. Issue 1 (January 2015) - Li, Chia-Ing; Li, Tsai-Chung; Liu, Chiu-Shong; Lin, Wen-Yuan; Chen, Ching-Chu; Yang, Sing-Yu; Lin, Cheng-Chieh; Shao., Jiaqing
<x xml:space="preserve">Abstract</x> Abstract The purpose of this study was to evaluate the relationship between glycated hemoglobin (HbA1c) and chronic obstructive pulmonary disease (COPD) in patients with type 2 diabetes. We conducted a retrospective cohort study involving 45, 753 patients with type 2 diabetes, who participated in the National Diabetes Case Management Program in Taiwan. HbA1c at baseline and COPD events over the subsequent years were analyzed. After multivariate adjustment, the COPD risk increased among patients with HbA1c levels <6.0%, compared with that in patients with HbA1c levels ranging from 6.0% to 7.0% (hazard ratio: 1.19, 95% confidence interval (CI): 1.06–1.34). Similarly, high HbA1c levels (≥10%) were independently associated with COPD (1.19, 95% CI: 1.06–1.32). A U-shaped relationship was observed between HbA1c levels and COPD incidence. HbA1c levels lower than 6.0% and higher than 10% are associated with an increased risk of COPD in patients with type 2 diabetes. These findings suggest that meeting the recommended HbA1c targets might reduce the risk of COPD, but care should be taken not to pose risks to this population.